Role of farnesoid X receptor in establishment of ontogeny of phase-I drug metabolizing enzyme genes in mouse liver - Peng, Lai (Acta Pharm Sin B, 2016)
The expression of phase-I drug metabolizing enzymes in liver changes dramatically during postnatal liver maturation. Farnesoid X receptor (FXR) is critical for bile acid and lipid homeostasis in liver. However, the role of FXR in regulating ontogeny of phase-I drug metabolizing genes is not clear. Hence, we applied RNA-sequencing to quantify the developmental expression of phase-I genes in both Fxr-null and control (C57BL/6) mouse livers during development. Liver samples of male C57BL/6 and Fxr-null mice at 6 different ages from prenatal to adult were used. The Fxr-null showed an overall effect to diminish the “day-1 surge” of phase-I gene expression, including cytochrome P450s at neonatal ages. Among the 185 phase-I genes from 12 different families, 136 were expressed, and differential expression during development occurred in genes from all 12 phase-I families, including hydrolysis: carboxylesterase (Ces), paraoxonase (Pon), and epoxide hydrolase (Ephx); reduction: aldoketo reductase (Akr), quinone oxidoreductase (Nqo), and dihydropyrimidine dehydrogenase (Dpyd); and oxidation: alcohol dehydrogenase (Adh), aldehyde dehydrogenase (Aldh), flavin monooxygenases (Fmo), molybdenum hydroxylase (Aox and Xdh), cytochrome P450 (P450), and cytochrome P450 oxidoreductase (Por). The data also suggested new phase-I genes potentially targeted by FXR. These results revealed an important role of FXR in regulation of ontogeny of phase-I genes.